The jacket - Clements, Andrew, 1949-2019 (Simon & Schuster Books for Young Readers, 2002)
Sixth-grader Phil comes to an awareness of his own racial prejudice after he sees Daniel, an African-American boy, wearing his brother's one-of-a-kind jacket and leaps to the conclusion that Daniel has stolen the coat.